Local Communities' Involvement, Relationship Quality, Self-Efficacy, and Sustainable Rural Tourism Development in Sarawak - Fong, Sook Fun (unimas, 2016)
Tourism has been recognized as an effective catalyst of socio-economic regeneration in rural areas. However, tourism has led to several negative impacts to rural tourism destinations in Sarawak. Therefore, sustainable rural tourism development is an important key concept to Sarawak tourism industry. This study investigate the relationships between local communities’ participation in decision making, knowledge sharing, empowerment, community knowledge of tourism, relationship trust, relationship commitment, relationship satisfaction, self-efficacy, and social, cultural, economic, and environmental sustainability in rural areas of Sarawak. A quantitative survey and participatory approach was conducted to obtain the data from the local communities. Statistical Package for Social Sciences (SPSS) version 22 and SmartPLS 2.0 (M3) were used to analyse the data collected from 458 respondents. Thirty-two hypothesized relationships were tested and thirteen of the hypotheses were supported. Thus, this study may be informative for future researchers and tourism stakeholders to have an in-depth understanding of the impact of local communities’ involvement, relationship quality, and self-efficacy on sustainable rural tourism development in Sarawak, Malaysia.